2007
DOI: 10.1590/s1516-35982007000100007
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de lisina digestível em rações, utilizando-se o conceito de proteína ideal, para suínos machos castrados de alto potencial genético para deposição de carne magra na carcaça dos 60 aos 95 kg

Abstract: RESUMO-Objetivou-se determinar o efeito de níveis de lisina digestível, utilizando-se o conceito de proteína ideal, sobre o desempenho e as características de carcaça de 40 leitões machos castrados (peso inicial de 30,02 + 1,38 kg e peso final 60,44 + 1,81 kg) de alto potencial genético para deposição de carne magra. Os animais foram distribuídos em delineamento de blocos ao acaso, com quatro tratamentos, cinco repetições e dois animais por unidade experimental. Os tratamentos consistiram de uma ração basal (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
10
2
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 20 publications
11
10
2
16
Order By: Relevance
“…The results of average daily weight gain were similar to those obtained by Oliveira et al (2003a,b) who observed pigs of 110 to 125 kg and 95 to 110 kg. However, the results differ from those reported by Abreu et al (2007), who observed a quadratic effect of diets on average daily weight gain, where the maximal response was obtained with 0.87% lysine and 3,250 kcal/kg, which corresponded to a daily intake of 24.67 g/day.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of average daily weight gain were similar to those obtained by Oliveira et al (2003a,b) who observed pigs of 110 to 125 kg and 95 to 110 kg. However, the results differ from those reported by Abreu et al (2007), who observed a quadratic effect of diets on average daily weight gain, where the maximal response was obtained with 0.87% lysine and 3,250 kcal/kg, which corresponded to a daily intake of 24.67 g/day.…”
Section: Resultscontrasting
confidence: 99%
“…Similar results were found by Carr et al (2005a), Marino et al (2007a, b) and Amaral et al (2009). Based on these results, we can infer that pigs fed diets supplemented with ractopamine have more efficient use of feed per unit weight gain than pigs that are fed diets without supplementation.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Rostagno et al (2005) recomiendan niveles de lisina digestible para cerdos de alto potencial genéti-co como 0,679% para cerdos en crecimiento de los 50 a los 70 kg de peso. Abreu et al (2007) estimaron en 0,93% el requerimiento de lisina digestible para cerdos de 60-95 kg de alto potencial genético para deposición de carne magra y Moreira et al (2004) recomiendan 0,75% de lisina total para cerdos machos en crecimiento.…”
Section: Introductionunclassified